Blanco, Mariela. El ángel y la mosca. Las poéticas de César Fernández Moreno, Joaquín Giannuzzi y Alfredo Veiravé (Anclajes, 2012)
Reseña crítica de Blanco, Mariela. El ángel y la mosca. Las poéticas de César Fernández Moreno, Joaquín Giannuzzi y Alfredo Veiravé